Lidocaine spray vs mepivacaine local infiltration for suturing 1st/2nd grade perineal lacerations: a randomised controlled non-inferiority trial - Stefano Restaino; Matilde Degano; Elisa Rizzante; Ginevra Battello; Federico Paparcura; Anna Biasioli; Martina Arcieri; Gabriele Filip; Luigi Vetrugno; Teresa Dogareschi; Tiziana Bove; Marco Petrillo; et al. (BMC, 2024)
Abstract Background Perineal lacerations are a very common complication of post-partum. Usually, the repair of 1st and 2nd-grade lacerations is performed after the administration of local anesthesia. Despite the great relevance of the problem, there are only a few studies about the best choice of local anesthetic to use during suturing. We performed a randomised controlled trial to evaluate the efficacy and safety of the use of a local anesthetic spray during the suturing of perineal lacerations in the post-partum. Methods We compared the spray with the standard technique, which involves the infiltration of lacerated tissues, using the NRS scale. 136 eligible women who had given birth at University Hospital of Udine were enrolled and randomly assigned to receive nebulization of Lidocaine hydrochloride 10% spray (experimental group) or subcutaneous/submucosal infiltration of mepivacaine hydrochloride (control group) during suturing of perineal laceration. Results The lacerations included 84 1st-grade perineal traumas (61.7%) and 52 2nd-grade perineal traumas (38.2%). All the procedures were successfully completed without severe complications or serious adverse reactions. There were no statistically significant differences between the two groups in terms of blood losses or total procedure time. Moreover, there were no statistically significant differences in terms of NRS to none of the intervals considered. Regarding the application of the spray in the B group, in 36 cases (52.9%) it was necessary to improve the number of puffs previously supposed to be sufficient (5 puffs). Just in 3 cases, an additional injection was necessary (4.4%). Conclusions Our study demonstrates that lidocaine spray alone can be used as a first line of local anesthetic during the closure of I-II-grade perineal lacerations, as it has comparable efficacy to mepivacaine infiltration. Trial registration The trial was recorded on https://clinicaltrials.gov . Identification number: NCT05201313. First registration date: 21/01/2022. Unique Protocol ID: 0042698/P/GEN/ARCS.